How Do Waterpipe Smoking Establishments Attract Smokers? Implications for Policy - Asfar, Taghrid (Subst Use Misuse, 2018)
BACKGROUND: Given the unique social nature of waterpipe smoking, an important factor contributing to its popularity is the spread of waterpipe establishments. OBJECTIVES: With a focus on implications for regulations, we conducted a qualitative assessment of customers’ online reviews on Yelp.com to gain insight into their positive and negative perceptions about waterpipe establishments and products, and identify features that are most important to them. METHODS: In June 2016, an online search of Yelp was conducted to identify waterpipe establishments in Miami, Florida. First, we collected information from the websites on establishments’ characteristics and their marketing practices. Then we selected customers’ water-pipe-related reviews and used an inductive qualitative method to code and identify key themes associated with positive and negative customers’ experiences. Thematic analysis was completed upon reaching saturation. The final coding scheme consisted of 32 codes within eight themes. RESULTS: The homepage of the establishment was used to promote special discounts and events, while the online waterpipe menu was used to promote the waterpipe products. Our thematic analysis indicated that the variety of flavored tobacco was the most rated positive factor to customers, while the low-quality charcoal and high price were the most negative factors. CONCLUSIONS/IMPORTANCE: Waterpipe online advertisements and promotions should be monitored and restricted. The availability of flavored tobacco, innovative device/accessories, affordable pricing, and charcoal quality are important domains for water-pipe establishments policy/regulation. Regulatory framework for waterpipe establishments should address the complex context of waterpipe including the venue (i.e., physical, website, menu), the tobacco, the device/accessories, and charcoal.